1992
DOI: 10.1577/1548-8675(1992)012<0204:vefdaa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Visually Estimating Fish Density at Artificial Structures in Lake Anna, Virginia

Abstract: Four artificial structures in Lake Anna, Virginia, were chosen to develop and refine a sampling technique designed to assess the effectiveness of structures in attracting fish. Several underwater observation techniques were tried before one suited to the prevailing restrictive and low‐visibility conditions was devised and applied to the four structures in summer and autumn 1988. Three consecutive fish counts were made at nine sampling locations per structure. Bluegills Lepomis macrochirus less than 15 cm in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…Despite being recognized as one of the most effective methods to survey structurally complex habitats (Seaman and Sprague 1991), it also is possible that visual censuses may have contributed at some level to the prevalence of small fishes in the artificial macrophytes in Boadella Reservoir. Although not observed in this study, Graham (1992) and Hayse and Wissing (1996) previously reported that fish [150 mm TL often moved further way from artificial structures as divers came closer (i.e. fright response), indicating that further research is necessary to elucidate the importance of that factor on fish use analysis of submerged habitats.…”
Section: Potential Of Artificial Macrophytes In Holding Fishcontrasting
confidence: 60%
“…Despite being recognized as one of the most effective methods to survey structurally complex habitats (Seaman and Sprague 1991), it also is possible that visual censuses may have contributed at some level to the prevalence of small fishes in the artificial macrophytes in Boadella Reservoir. Although not observed in this study, Graham (1992) and Hayse and Wissing (1996) previously reported that fish [150 mm TL often moved further way from artificial structures as divers came closer (i.e. fright response), indicating that further research is necessary to elucidate the importance of that factor on fish use analysis of submerged habitats.…”
Section: Potential Of Artificial Macrophytes In Holding Fishcontrasting
confidence: 60%
“…When performing visual counts on artificial fish habitats, Graham (1992) found that fish dispersed by divers would return in 3-5 min. Therefore, after DIDSON deployment, we waited 5 min before recording fish counts.…”
Section: Methodsmentioning
confidence: 99%
“…In general, the average number of individuals and species attracted increases with the structural complexity achieved by increasing the volume, size, and surface area of habitat enhancement structures (Wickham et al 1973;Rountree 1989;Graham 1992). Further, fish abundance varies with structure interstice size (the space within structures) in a complex fashion (Wege and Anderson 1979;Johnson et al 1988;Lynch and Johnson 1989;Walters et al 1991).…”
Section: Variable Effects Of Habitat Enhancement Structuresmentioning
confidence: 99%